Intellectual, academic, and psychosocial self-care achievements among children with autism - Vidal, Lutze-Sol Aplaon (2012)
Progress in intellectual, academic and psychosocial-self-care achievements among 30 children with autism (CWA) within five years (2006-2010) was determined utilizing inter-correlations through Pearson r. Univariate repeated-means analysis was also used to determine if scores significantly differed from one another. Another objective was to find out if there were significant differences in intellectual, academic and psychosocial self-care achievements among CWA in terms of: a) the type of SPED tutorials (i.e., with or without behavior coaching), b) school placement (i.e., big or small school), and c) the type of behavioral intervention (i.e., occupational therapy, applied behavior analysis or both). To determine this, repeated-measures ANOVA was used. Results indicated that there were significant increases in the CWA's intellectual, academic and psychosocial-self-care achievements within the five years while there were no significant differences among the selected factors mentioned in terms of the CWA's intellectual, academic and psychosocial-self-care achievements except for shift in placement from small to big school. Implications and recommendations based on the results are forwarded.
Keywords: Academic achievement; Autistic children